E-Wallet: A Study on Cashless Transactions Among University Students [version 1; peer review: 2 approved, 1 not approved] - Han Hui Yi; Hazlaili Hashim; Anushia Chelvarayan; Sook Fern Yeo (F1000Research, 2022)
E-wallet is an application that enable users to download payment cards using a mobile device. It is a new trend for consumers to use an e-wallet application to replace the traditional payment method. With E-wallet, a user does not need to bring cash or a credit card along with them. It enables users to make purchases in a more convenient way. Hence, this research analyses the factors that affect university students’ intention to use e-wallet. The Technology Acceptance Model (TAM) serves as the theory underpinning this research A total of 140 respondents from a Malaysian private institution participated in this study. Convenience sampling was used to select samples, and respondents completed the questionnaire using a Google form and a paper and pencil approach. The questionnaire was created using a nominal scale and a five-point Likert scale. Descriptive analysis, reliability analysis, and multiple regression analyses were utilised to analyse the data in this study. Students, supervisors, academics, researchers, learning institutions, commercial organisations, and the government will all benefit immensely from the data and information gathered from this study as we will be able to examine and understand the factors that influence students' decision to use an e-Wallet for their daily financial operations. This study, however, has certain limitations as it does not reflect the complete student population in Malaysian tertiary education and only examines four variables: perceived usefulness, perceived ease of use, perceived risk, and trust. Future studies could focus on other impacting elements such as risk, complexity, pervasive technology use and tech-savvy future generations.